Growth Increment and Genetic Variability in Relation to Age in Saplings of Eucalyptus tereticornis Sm. - Krishnaswami, S.; Srinivasan, V. M.; Vinaya Rai, R. S. (Indian Forester, 1982)
Studies were carried out at the Forestry Research Station. Mettupalayam to assess the variation in growth components at 6 and 12 months after planting and growth increment in progenies of eight plus trees of E. tereticornis of Arakku Valley, Andhra Pradesh. Saplings of hulked seed served as control. The genetic parameters of growth components in relation to age were also determinted. Though no progeny proved superior to the bulk population in respect of any of the growth attribute investigated, in terms of diameter increment, Those of T4 T6 and T7 scored over others. Heritability of plant height and base diameter did not vary with age. Base diameter was characterised by high heritabllity and low GA suggesting the high heritability to be due to non-additive genes.